Development of a nested PCR for detection of Bovine herpesvirus-1 (BHV-1) in bovine nasal secretion and semen - Saepulloh, Muharam; Adjid, R.M Abdul; T. Wibawan, I Wayan; ., Darminto (Indonesian Animal Sciences Society, 2008)
A nested polymerase chain reaction (nPCR) assay for detection of Bovine herpesvirus-1 (BHV-1) in bovine semen and nasal secretions was successfully developed. The nested Polymerase Chain Reaction was based on external and internal primers from the viral gD glycoprotein gene. This nPCR assay was 1000-fold more sensitive than using PCR external primer. The nested PCR has a detection limit as low as 5 ag/ml pure BHV-1 DNA and 100,75 TCID50/500 mL BHV-1 infected cells. On the other hand,Â PCR using external primer had detection limit of about 5 fg/ml pure BHV-1 DNA. Specificity studies showed that nPCR could only detect BHV-1, whereas BHV-4, PRV, PI-3 and BRSV can not be detected. In addition, nPCR was also capable in detecting BHV-1 in nasal secretion samples from animal without clinical signs. A total of 405 samples consisted of 381 nasal secretion and 24 fresh semen samples have been tested with the nPCR. The result revealed that from 381 nasal secretion samples tested, 14 samples showed to be positive (3.68%), consisting of 13 out of 294 (4.42%) nasal secretion samples collected from Pangalengan West Java, and 1 out of 87 (1.54%) samples collected from Bogor. Furthermore, 2 out of 11 (18.18%) extended semen samples collected from Bogor and 2 out of 13 (15.38%) fresh semen samples collected from Pasuruan also showed to be positive. In addition, the nPCR was faster and easier to perform than the standard viral isolation test. It is concluded that, the nPCR can be used as test of choice for routine diagnosis of BHV-1. Key Words: Nested PCR, BHV-1, Semen, Glycoprotein D Gene, TCID50